Synthesis of Surfactants Derived from 2-Mercaptobenzimidazole and Study of Their Acute Toxicity and Analgesic and Psychotropic Activities - Terence Nguema Ongone; Latyfa El Ouasif; Mostafa El Ghoul; Redouane Achour; Hind Chakchak; Meryem El Jemli; Yahia Cherrah; Katim Alaoui; Amina Zellou (Biochemistry Research International)
The aim of the present study is to synthesize cationic salts from a relatively toxic compound named 2-mercaptobenzimidazole and to evaluate some of their pharmacological properties. The acute toxicity of these salts is evaluated according to OECD 423 Guidelines at the doses of 300 and 2000 mg/kg; their peripheral analgesic effect is studied using the Koster test at the therapeutic dose of 200 mg/kg and their sedative action is evaluated using Traction, Chimney, Hole-board, and Rotarod tests at the doses of 200 and 400 mg/kg. All synthesized molecules show no acute toxicity according to OECD Code 423 guidelines at doses ranging from 300 to 2000 mg/kg and do not cause any obesity or anorexia. Also, the results of the Koster test show that the studied compounds have an average analgesic effect at the dose of 200 mg/kg compared to acetylsalicylic acid. In addition, the elaborated compounds have shown a moderate sedative effect at the dose of 400 mg/kg, in comparison to 2-mercaptobenzimidazole (400 mg/kg) and Bromazepam (20 mg/kg). These compounds have no cataleptic and hypnotic effects on the central nervous system at the doses of 200 and 400 mg/kg. These results argue in favor of a possible integration of the most active salts tested in the pharmaceutical industry owing to their analgesic and sedative effects.